Pengaruh Media Audio Visual Dan Kompetensi Pedagogik Guru Terhadap Aktivitas Belajar Siswa SMA Negeri 1 Bandar Khalifah - Mauliza; Nasution, Herry Syahbannuddin; Parinduri, Sari Atika (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
The research aims to find out about "The influence of audio-visual media and teacher pedagogical competence on the learning activities of students at SMA Negeri 1 Bandar Khalifah".Audio visual learning media is a learning media that can create a pleasant atmosphere because students like watching learning videos.Pedagogical Competencies Mastering the characteristics of students Mastering learning theories and principles of educational learning Curriculum development Learning activities that educate developing potential students communication with students Assessment and evaluation.Learning activities are learning processes carried out by teachers in such a way as to create active students asking questions, questioning and putting forward ideas. Martimis Yamin explained that learning activities are students' efforts in the learning process to build knowledge within themselves. In the learning process there are changes and improvements in the quality of abilities such as having the courage to ask questions, expressing opinions, listening to the teacher's explanations well, and doing assignments on time. Learning activities are principles or principles that are very important in teaching and learning interactions. In other words, there is no learning if there is no activity, because in principle learning is doing.